THE EUROPEAN ARREST WARRANT AND THE PROTECTION OF FUNDAMENTAL RIGHTS: THE FAMOUS JUDGMENT IN ARANYOSI AND CALDARARU CASE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Since its adoption, the Framework Decision on European Arrest Warrant (FDEAW) is controversial, as the execution of the European Arrest Warrant (EAW) according the mutual recognition principle could be in conflict with the fundamental rights of the concerned person. It is assumed that the national authorities of member-states of the European Union (EU) comply with the right of fair trial and other fundamental rights. However, in practice this assumption does not necessary holds true. Also, the EAW system triggered debates regarding its lack of sufficient protection for human rights. The Court of Justice of the EU (CJEU) did not seem particularly sensitive to the criticism and was more worried about the effectiveness of the EAW system as a whole, while the EU institutions were completely aware when the EAW system was created and ignored the issue of fundamental rights protection. The FDEAW contains provisions for protection of procedural rights and the right of fair trial, but EU institutions decided that not all violations on fundamental rights may justify the non-execution of EAW. The paper presents personal views regarding the EAW through the famous Aranyosi and Caldararu case that reveal an upward trend. After this judgment, the CJEU gives more significance to human rights. It explains how the CJEU constructed different FDEAW provisions and whether and to what extent national courts used the preliminary ruling procedure regarding criminal law measures vis-à-vis protection of fundamental rights.